A novel displacement-based Trefftz plate element with high distortion tolerance for orthotropic thick plates - Chenfeng Li (Engineering Analysis with Boundary Elements, 2019)
In this work, a simple but robust 4-node displacement-based Trefftz plate element is proposed for efficiently analysis of orthotropic plate structures. This is achieved via two steps. First, the element's deflection and rotation fields are directly formulated at the base of the Trefftz functions of the orthotropic Mindlin–Reissner plate. Second, to ensure the convergence property and further enhance the element performance, the generalized conforming theory is employed to satisfy the requirement for interelement compatibility in weak sense. The resulting displacement-based element belongs to the nonconforming models on coarse meshes and gradually converges into a conforming one with the mesh refinement. Numerical benchmarks reveal that the new element can produce high precision results for both displacement and stress resultant. Moreover, it is free of shear locking and has good tolerances to mesh distortions.